Sytuacja finansowa gospodarstw domowych w Polsce w latach 2000-2004 - Muszyńska, Władysława ("The Financial Situation of Households in Poland (In the Years 2000-2004)", 2006)
The aim of the article is to evaluate the financial situation of householders in Poland between 2000 and 2004. Chosen factors shaping the level, structure and diversity of living conditions in cross section of socio-economic types of households were analyzed. Attention was paid to varied methodology of the households incomes measurement applied by research centres leading to the lack of comparability of results. An example of calculating an income being at a disposal of a household with the use of the so called OECD equivalence applied by GUS (the Main Office of Statistics) was shown. The increase in the time of propensity for consumption of economically active households (people working on their own) was described. The analysis of aims and forms of saving money and the reasons for indebting of households enabled to evaluate the way of managing the households finance. It helped to find out the causes of difficult financial situation of Polish households. Summing up, it was shown that incomes and financial situation are the reasons for dissatisfaction for over 50 per cent of the Polish society. This fact should be the basic premise for the changes in the existing income and social policy of state, taking into account equalizing living conditions in the EU countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 155-174